2002
DOI: 10.1159/000064052
|View full text |Cite
|
Sign up to set email alerts
|

Most X;autosome translocations associated with premature ovarian failure do not interrupt X-linked genes

Abstract: Balanced translocations with breakpoints in a critical region of the X chromosome, Xq13→q26, are associated with premature ovarian failure (POF). Translocations may cause POF either by affecting expression of specific X-linked genes essential for maintenance of normal ovarian function or by a chromosomal effect such as inhibition of meiotic pairing or altered X inactivation. We previously mapped seven Xq translocation breakpoints associated with POF to ∼75-kb intervals. One translocation disrupted an aminopept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 22 publications
3
42
0
2
Order By: Relevance
“…Only the DIAPH2 gene, a human homolog of the Drosophila melanogaster diaphanous gene affecting spermatogenesis and oogenesis, was found disrupted by a breakpoint in a family with POI, but no mutation demonstrated its role in ovarian function nor that of the others candidates. However, most breakpoints described in POI patients were frequently mapped in Xq21, outside of genic regions, consistent with models for POI associated with X to autosome translocations that involve extra X chromosome effects (Mumm et al 2001, Prueitt et al 2002. These observations suggest the hypothesis that chromosomal rearrangements due to an epigenetic effect of the active X chromosome may account for a position effect on promoters of autosomal genes when involved in balanced translocations (Rizzolio et al 2007).…”
Section: Syndromic Poisupporting
confidence: 76%
“…Only the DIAPH2 gene, a human homolog of the Drosophila melanogaster diaphanous gene affecting spermatogenesis and oogenesis, was found disrupted by a breakpoint in a family with POI, but no mutation demonstrated its role in ovarian function nor that of the others candidates. However, most breakpoints described in POI patients were frequently mapped in Xq21, outside of genic regions, consistent with models for POI associated with X to autosome translocations that involve extra X chromosome effects (Mumm et al 2001, Prueitt et al 2002. These observations suggest the hypothesis that chromosomal rearrangements due to an epigenetic effect of the active X chromosome may account for a position effect on promoters of autosomal genes when involved in balanced translocations (Rizzolio et al 2007).…”
Section: Syndromic Poisupporting
confidence: 76%
“…32 Molecular mapping of several of these breakpoints have shown that they are scattered over the entire critical region, supporting the idea that integrity of a specific chromosomal domain may be important for the development of female germ cells. 33 Since the chromosome 1 breakpoints in male infertility do not seem to be associated with any specific chromosomal region(s), either at the cytogenetic or at the molecular level, we suggest that chromosome 1 harbours a large chromosomal domain, the integrity of which is important for normal spermatogenesis.…”
Section: Discussionmentioning
confidence: 81%
“…[Cremers et al 1990], and DIAPH2 (MIM * 300108) in Xq22 [Bione et al 1998]. However, most of the breakpoints mapped in the Xq region described in POF patients are intergenic [Mumm et al 2001;Prueitt et al 2002]. Only the DIAPH2 gene was disrupted by translocation in a family with POF affecting oogenesis [Bione et al 1998].…”
Section: Resultsmentioning
confidence: 99%